2011
DOI: 10.1111/j.1542-2011.2011.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers of Independent Decisions by Midwives During Labor and Birth

Abstract: When making labor management decisions, midwives are affected by their trust in birth, the woman, the health care team, and the birth environment. Midwives report more resistance when making labor management decisions in hospitals. The findings of this study provide insight into both the decision making of midwives and how factors in different environments, in this case hospitals and freestanding birth centers, influence the ability of midwives to make independent labor management decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 19 publications
1
52
0
1
Order By: Relevance
“…Respect for different members within the delivery team contributes to an affirmative work environment, which is highly valued. Similar findings were reported by Everly (), where great teamwork experienced within free‐standing birth centres positively affected midwives' decisions on labour management. Receiving support from colleagues and other health care professionals enabled midwives to provide better labour support to birthing women (Carolan‐Olah et al, ).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Respect for different members within the delivery team contributes to an affirmative work environment, which is highly valued. Similar findings were reported by Everly (), where great teamwork experienced within free‐standing birth centres positively affected midwives' decisions on labour management. Receiving support from colleagues and other health care professionals enabled midwives to provide better labour support to birthing women (Carolan‐Olah et al, ).…”
Section: Resultssupporting
confidence: 85%
“…Specifically, culture and women's preferences can influence the types of positions utilized during birthing (de Jonge et al, ). Therefore, midwives felt that decision‐making around childbirth should consider women's wishes and choices (Everly, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A midwifery strategy for coping in the AMU/FMU setting can be to adhere to a philosophy that underpins and supports normality and work in accordance with this philosophy (or choose to work in a obstetric unit). To work in line with a midwifery philosophy in obstetric units is described as challenging in many aspects (6,10,20,30). It is worth noting that O'Connell and Downe's metasynthesis showed that midwives, rather than doctors, are the dominant influence in the practice of medicalised birth care (10).…”
Section: Discussionmentioning
confidence: 99%
“…Care in midwifery units is associated with promoting the midwife-mother relationship, facilitating a sense of higher satisfaction and autonomy for both mothers and midwives (13,(15)(16)(17)(18)(19). An American study noted that midwives' experiences of the birth centre atmosphere are described as relaxing, quiet, and less restricted with respect to time and guidelines (20). A British report which explores hospital alongside midwifery units, shows that philosophy and practice are closely interrelated and have significant value for midwives and that working in this kind of units enhances their autonomy (21).…”
Section: Introductionmentioning
confidence: 99%